DIGITAL MARKETING & BUSINESS OF E-COMMERCE ON PANDEMIC COVID19 - Muhammad Rizki; Dian Octaviani (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The aim of this paper is to examine the solutions adopted by MSMEs to survive and recover from the Covid19 pandemic crisis. The study's focus is on 37 thousand MSMEs that have been directly impacted by the pandemic. Literature was used as a method. According to this study, customers practically forget about a brand during a pandemic, but that brand awareness will be restored through digital advertising. The expansion of online customers is no longer being driven by the millennial generation. Some SMEs have gone out of business. But there aren't many who climb and then expand. MSMEs alter their manufacturing processes by lowering the amount of goods produced while also innovating to improve their competitiveness. On the other hand, digital marketing has been used extensively to raise client awareness. Marketplaces, as an e-commerce manifestation, are employed as a kind of innovation or change in sales tactics.